1997
DOI: 10.1073/pnas.94.17.9069
|View full text |Cite
|
Sign up to set email alerts
|

Propeptide and glutamate-containing substrates bound to the vitamin K-dependent carboxylase convert its vitamin K epoxidase function from an inactive to an active state

Abstract: The vitamin K-dependent ␥-glutamyl carboxylase catalyzes the posttranslational conversion of glutamic acid to ␥-carboxyglutamic acid in precursor proteins containing the ␥-carboxylation recognition site (␥-CRS). During this reaction, glutamic acid is converted to ␥-carboxyglutamic acid while vitamin KH 2 is converted to vitamin K 2,3-epoxide. Recombinant bovine carboxylase was purified free of ␥-CRS-containing propeptide and endogenous substrate in a single-step immunoaffinity procedure. We show that in the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 31 publications
(15 reference statements)
2
32
0
Order By: Relevance
“…The results from a previous study point toward a mechanism with the ordered addition of substrates to carboxylase: the exact order of binding, however, could not be clearly shown (41). In addition, the finding that no significant epoxide formation occurs in the absence of the glutamate substrate (42), suggests it is possible that the glutamate must bind to carboxylase before vitamin K for normal function. This order may be reversed at high concentrations of vitamin K, inhibiting the reaction.…”
Section: Vitamin K-dependent Carboxylase Glutamate Binding Residuesmentioning
confidence: 52%
“…The results from a previous study point toward a mechanism with the ordered addition of substrates to carboxylase: the exact order of binding, however, could not be clearly shown (41). In addition, the finding that no significant epoxide formation occurs in the absence of the glutamate substrate (42), suggests it is possible that the glutamate must bind to carboxylase before vitamin K for normal function. This order may be reversed at high concentrations of vitamin K, inhibiting the reaction.…”
Section: Vitamin K-dependent Carboxylase Glutamate Binding Residuesmentioning
confidence: 52%
“…Sugiura et al (10) showed that carboxylase does not catalyze epoxidation of KH 2 in the absence of propeptide or FLEEL. The reaction is fastest, ϳ10-fold faster than with any single component, with both FLEEL and propeptide.…”
Section: Discussionmentioning
confidence: 99%
“…7, a and b). The cells contain endogenous carboxylase, whose ability to recycle KH 2 to KO was unknown because the carboxylase requires activation by VKD proteins (29,30), which were present in only trace amounts in these cells (31). Therefore, the experiment was repeated in cells pretreated with carboxylase siRNA prior to the addition of KO.…”
Section: Vkorc1 Reduces Ko To Kh 2 To Drivementioning
confidence: 99%